Web service for enterprise resource management systems - Tarasenko, A.D.; Doroshenko, A.Yu. (Інститут програмних систем НАН України, 2022)
A web service for enterprise resource management systems has been developed, which allows creating and managing fast secure enterprise resource management systems based on user-required modules. The uniqueness of the service is that in addition to the fact that it contains most of the existing standards and capabilities of other ERP systems from other IT companies, it has a significant advantage - there is no need to address IT-specialists for the development and configuration of ERP systems for the needs of the end user in its use. The main website of the web service has been developed, which provides authentication and authorization; installer application for creating and running ERP system; ERP server application, and client application for interaction with ERP system. Functional testing of the developed web service was carried out by testing each application separately and in a joint relationship. Thanks to the concept of modularity, this system is easily supplemented and expanded. In the future, this service can be supplemented with new functionality, depending on business requirements.Problems in programming 2022; 2: 47-56